2019
DOI: 10.1109/access.2019.2949343
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Single Ripe Tomato on Plant Combining Faster R-CNN and Intuitionistic Fuzzy Set

Abstract: Fast and accurate detection of ripe tomatoes on plant, which replaces manual labor with a robotic vision-based harvesting system, is a challenging task. Tomatoes in adjacent positions are easily mistaken as a single tomato by image recognition methods. In this study, a ripe tomato detection method that combines deep learning with edge contour detection is proposed. Our approach efficiently separates target tomatoes from overlapping tomatoes to detect individual fruits. This approach yields several improvements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…From the brief introduction of several commonly used models described above, we know that deep-learning technology has a powerful role in image classification, regression and segmentation. Furthermore, there are also many other kinds of network structures that are applied, such as single shot multibox detection (SSD) 56 , long short-term memory (LSTM) 32 , you only look once (YOLO, source code is available at: http://pjreddie.com/yolo/ ) 57 , regions-CNN (R-CNN) 58 , fast region-based CNNs (Fast R-CNN, source code is available at: https://arxiv.org/abs/1504.08083 ) 33 , faster region-based CNNs (Faster-RCNN, source code is available at: https://github.com/shaoqingren/faster_rcnn (in MATLAB) and at https://github.com/rbgirshick/py-faster-rcnn (in Python)) 44 , 59 , 60 , and so on. In addition, the processed data types are not simply limited to RGB images but can also include any other data forms, such as video, hyperspectral images, and spectral data.…”
Section: Brief Overview Of Deep Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…From the brief introduction of several commonly used models described above, we know that deep-learning technology has a powerful role in image classification, regression and segmentation. Furthermore, there are also many other kinds of network structures that are applied, such as single shot multibox detection (SSD) 56 , long short-term memory (LSTM) 32 , you only look once (YOLO, source code is available at: http://pjreddie.com/yolo/ ) 57 , regions-CNN (R-CNN) 58 , fast region-based CNNs (Fast R-CNN, source code is available at: https://arxiv.org/abs/1504.08083 ) 33 , faster region-based CNNs (Faster-RCNN, source code is available at: https://github.com/shaoqingren/faster_rcnn (in MATLAB) and at https://github.com/rbgirshick/py-faster-rcnn (in Python)) 44 , 59 , 60 , and so on. In addition, the processed data types are not simply limited to RGB images but can also include any other data forms, such as video, hyperspectral images, and spectral data.…”
Section: Brief Overview Of Deep Learningmentioning
confidence: 99%
“…In another study, Sun et al 73 used a CNN based on the original Faster R-CNN algorithm to detect and identify flowers and mature (red) and immature (green) fruits of tomatoes. Hu et al 60 introduced a method that combined intuitionistic fuzzy set (IFS) theory with the Faster R-CNN model to detect individual ripe tomatoes. The ripe tomato image dataset, which includes adjacent, separated, leaf-shaded, and overlapped images, was used to obtain exact values of the height and width, and these data were then analyzed to evaluate the overall performance of the proposed detection model.…”
Section: Applications Of Deep Learning In Horticulture Cropsmentioning
confidence: 99%
“…Liu et al [ 12 ] studied an algorithm combining a coarse-to-fine scanning method and a false-color removal method to detect mature tomatoes. To achieve accurate ripe tomato detection, Hu et al [ 13 ] suggested a method that combines a deep learning algorithm and an edge-contour analysis method. Sun et al [ 14 ] proposed an improved feature-pyramid-network-based tomato organ recognition method.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional image recognition mainly includes four links: image acquisition, image preprocessing, feature extraction, and pattern matching, while the main complex work focuses on the image preprocessing and feature extraction stages. The authors of [27] proposed a detection method that combines Fast R-CNN with an adaptive threshold intuitionistic fuzzy set to segment and recognizes overlapping or occluded tomatoes on plants.…”
Section: Related Work 21 Image Processingmentioning
confidence: 99%